Yeast profile of Capiz, Philippines water kefir grains in a three-level propagation scheme - Rafael, Hannah Ruby P. (College of Home Economics, University of the Philippines Diliman, 2013)
The present study established the major yeast strains found in Capiz water kefir grains obtained in 2012 using a standardized 3-level propagation scheme in 5% (w/v) Philippine raw brown sugar solution. The kefir grains used in the study had the following physical and microbiological characteristics at the dried state: dominant 131 U pantone color, grain size of 2.4-6.9mm in diameter, 0.766 Aw and 11.06% moisture content (dry basis). The mean APC, MPC, YMC values were 1.22x107 cfu/g, 9.53x107 cfu/g, 1.60x105 cfu/g, respectively. The protection given by the polysaccharide to the microorganisms in the dried grains was used to explain the detectable grain viable microbial counts. The kefir grains achieve a maximum hydration after of 12-24h activation in 5% brown sugar solution at 30±20C. The recorded biomass increase was attributed to the yeast enhancement for LAB to produce exopolysaccharide (EPS) during propagation. The decrease in APC and MPC of kefir grains across propagation was attributed to the dispersion of microorganisms to the medium. The observed increase in YC of the kefir grains across propagation was related to the strong adherence of the yeast to the matrix and the favorable environment for proliferation. The microbial profile of the supernatant at the 3rd level of propagation was considered to be due to the microbial dispersion to the medium of the grain microorganism. The identified major yeast strains found in the kefir grains from the 3rd level of propagation were Candida colliculosa and Saccharomyces cerevisiae that comprised about 7-20% and 30-80% of the yeast population 1.12x107, respectively. Validation of the study and complete yeast identification from the grains and supernatant was recommended in the study.